INTERNALIZATION OF RELIGIOUS VALUES TO GROW STUDENT CHARACTER IN PUBLIC SCHOOL - Fauzi, Ahmad (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
Western’s life style in daily life without filtering whether it is appropriate or not according to Indonesian culture. Furthermore, it may cause religious decadence in which Indonesian people has been well-known as the obedient muslim for decades. The school has been considered as the big role to overcome any problem caused by teenagers. Therefore, investing religious values for improving student’s attitude is the real effort which is very important in order to grow student’s awareness. The research aims to describe clearly about Internalization religious values for improving student’s attitude in the school. More specifically, this research focuses on 1) How does the process of internalizing religious values to foster the character of students in public schools? 2) How is the impact of internalization of religious values to foster the character of students in public schools? The conclusion of this research are: 1) The process of internalization of religious values to foster the character of students through 5 stages: a) Selection field; b) Selection Values; c) Nursery Values; d) Planting Values; e) Treatment Values. 2) The impact of internalization of religious values to foster the character of students are: a) Harvest Values; b) Post Harvest Values.